2020
DOI: 10.1016/j.jbspin.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of bone-resorptive lesion volume in osteonecrosis of the femoral head using micro-computed tomography

Abstract: Objectives To quantify the volume of bone-resorptive lesions in post-collapse osteonecrosis of the femoral head (ONFH) using micro-computed tomography (micro-CT) and assess their characteristics in postcollapse ONFH.Methods We investigated 35 femoral heads resected from 35 patients with ONFH (20 men and 15 women; mean age, 47.2 years). On each of seven coronal high-resolution micro-CT slices of the femoral head, the bone-resorptive areas were extracted using bone microstructure measurement software. Next, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Therefore, apart from the eccentrically located necrotic lesions, the HU values in the current study may well reflect those of extended necrotic lesions that have a high possibility of collapse. We focused on the anterosuperior portion of the femoral head because this is where collapse usually occurs, and thus examining this region should provide the most information about the decrease in HU values in pre‐collapse ONFH 15,30 . Finally, we did not actually demonstrate that the HU values of the necrotic lesion decreased after collapse in ONFH.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, apart from the eccentrically located necrotic lesions, the HU values in the current study may well reflect those of extended necrotic lesions that have a high possibility of collapse. We focused on the anterosuperior portion of the femoral head because this is where collapse usually occurs, and thus examining this region should provide the most information about the decrease in HU values in pre‐collapse ONFH 15,30 . Finally, we did not actually demonstrate that the HU values of the necrotic lesion decreased after collapse in ONFH.…”
Section: Discussionmentioning
confidence: 91%
“…We focused on the anterosuperior portion of the femoral head because this is where collapse usually occurs, and thus examining this region should provide the most information about the decrease in HU values in pre-collapse ONFH. 15,30 F I G U R E 6 Differences in Hounsfield unit (HU) values of the lateral boundary between osteonecrosis of the femoral head (ONFH) patients with and without subsequent collapse after CT. The mean HU value of the lateral boundary in 12 ONFH patients with subsequent collapse within one year after CT is 350.1 ± 139.1 (153.6-591.3), while that in 15 patients without collapse after CT is 240.3 ± 84.9 (94.5-393.7).…”
Section: Differences In Hu Values Of the Lateral Boundary Between Omentioning
confidence: 99%
“…The pathologic characteristics of bone-resorptive lesions, in which trabecular structure was no longer present, are noncavitary and contain loose fibrous elements 10,11 . By using micro-CT imaging of the femoral head in ARCO stage III from total hip arthroplasty, Hamada et al 6 and Baba et al 7 found that the bone resorption area can lead to the initiation of subchondral fracture and accelerate the progress of collapse. In addition, Gao et al 8 also demonstrated that the femoral head with osteonecrosis complicating by cystic bone-resorptive area is more likely to accompany microfracture and crescent sign, which could hint that the femoral head loses its stability and proceeds to collapse more quickly.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, others studies demonstrated that when the necrotic lesions involved more anterolateral femoral head, collapse will almost be inevitable 4 , 5 . Besides the size and location of the necrotic lesion, previous studies have demonstrated that subchondral fracture and collapse are closely related to bone‐resorptive lesions, suggesting the importance of bone‐resorptive lesions on the collapse progression 6 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed that the reactive interface and normal region displayed a less sclerotic microarchitecture in GIONFH as compared with AIONFH, exhibiting a lower bone volume fraction, less trabecular number, and wider trabecular space, especially in the Cen-Cen region. The deteriorated microarchitecture has been reported to play a pivotal role in the failure of mechanical stabilization in the femoral head, and eventually leads to the progression of collapse 52 . The alterations of microstructure may be due to the distinct bone remodeling status 53 , which could be in uenced by different reagents that affect bone metabolism such as glucocorticoid and alcohol.…”
Section: Discussionmentioning
confidence: 99%